2022
DOI: 10.3390/medicina58121752
|View full text |Cite
|
Sign up to set email alerts
|

Central Sensitization Is Associated with Inferior Patient-Reported Outcomes and Increased Osteotomy Site Pain in Patients Undergoing Medial Opening-Wedge High Tibial Osteotomy

Abstract: Background and Objectives: Studies have shown that centrally sensitized patients have worse clinical outcomes following total knee arthroplasty (TKA) than non-centrally sensitized patients. It is unclear whether central sensitization (CS) affects patient-reported outcomes (PROs) and/or level of osteotomy site pain in patients undergoing medial opening-wedge high tibial osteotomy (MOWHTO). The purpose of this study was to determine whether CS is associated with PROs and osteotomy site pain following MOWHTO. Mat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(10 citation statements)
references
References 48 publications
3
7
0
Order By: Relevance
“…The primary outcome of this study is concordant with previous studies [15, 16, 19, 29] indicating that a high CSI score is correlated with unfavourable outcomes following surgeries for KOA treatment, even after adjusting for confounding factors. While the majority of similar studies focus on TKA [16, 19, 29], there is only one existing study by Kim et al that addresses OWHTO.…”
Section: Discussionsupporting
confidence: 91%
See 3 more Smart Citations
“…The primary outcome of this study is concordant with previous studies [15, 16, 19, 29] indicating that a high CSI score is correlated with unfavourable outcomes following surgeries for KOA treatment, even after adjusting for confounding factors. While the majority of similar studies focus on TKA [16, 19, 29], there is only one existing study by Kim et al that addresses OWHTO.…”
Section: Discussionsupporting
confidence: 91%
“…While the majority of similar studies focus on TKA [16, 19, 29], there is only one existing study by Kim et al that addresses OWHTO. In their study, Kim et al [15] reported that patients with a high pre‐operative CSI score (≥ 40) experienced poorer patient‐reported outcomes and higher levels of pain two years after the surgery. However, it should be noted that there is a discrepancy in the cut‐off scores between Kim et al and this present study.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Thus, considering these confounding factors is essential to rigorously examine the association between these two. Additionally, central sensitization (CS) has also received attention recently as a factor that strongly influences PROMs [ 25 , 26 , 27 , 28 ]. CS is defined as the increased responsiveness of nociceptive neurons in the central nervous system to normal or subthreshold afferent input by the International Association for the Study of Pain [ 29 ].…”
Section: Introductionmentioning
confidence: 99%